2022
DOI: 10.1016/j.jgr.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Possibility as role of ginseng and ginsenosides on inhibiting the heart disease of COVID-19: A systematic review

Abstract: Coronavirus has been spreading rapidly around the world since it broke out in China in 2019. Respiratory diseases caused by coronavirus infection cause various diseases ranging from asymptomatic subclinical infections to severe pneumonia and cardiovascular complications, leading to death. In this regard, natural products are being studied to prevent various diseases caused by COVID-19. In current review, we would like to present mechanisms related to the inhibition of heart disease in ginseng and ginsenoside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…[ 16 ] Ginsenosides, the main active ingredient in ginseng, account for 4% of the total ginseng, which can improve the immunity of the body [ 17 ] ; the active ingredients of aconite have cardiotonic and antiarrhythmic effects. [ 18 ] This is the first meta-analysis to evaluate the efficacy and safety of Shenfu injection for STEMI after primary PCI. The results of our study need to be validated in larger trials (particularly confining to patients with estimated larger infarct size).…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Ginsenosides, the main active ingredient in ginseng, account for 4% of the total ginseng, which can improve the immunity of the body [ 17 ] ; the active ingredients of aconite have cardiotonic and antiarrhythmic effects. [ 18 ] This is the first meta-analysis to evaluate the efficacy and safety of Shenfu injection for STEMI after primary PCI. The results of our study need to be validated in larger trials (particularly confining to patients with estimated larger infarct size).…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, 20(S)-ginsenoside Rg3 and 20(R)-ginsenoside Rg3 effectively suppress the binding between the spike glycoprotein, the binding protein of SARS-CoV-2, and the ACE2 receptor. This action may play a key role in the treatment of papulovesicular exanthem by preventing entry of the virus into keratinocytes [ 49 ].…”
Section: Pathogenesis Of Covid-19-related Skin Diseases and Therapeut...mentioning
confidence: 99%
“…According to one study, the oral medication isotretinoin, which is used to treat acne lesions, was identified as a treatment for COVID-19, acting by downregulating the expression ACE2 receptors, preventing SARS-CoV-2 entry into vulnerable cells [ 106 ]. Similarly, ginsenosides are known to block the receptor-binding domain (RBD)-ACE2 interaction by suppressing the RBD on the coronavirus spike glycoprotein [ 107 ]. One study showed that 20(S)-ginsenoside Rg3 and 20(R)-ginsenoside Rg3 repressed viral infection in cells that specifically express the receptors [ 35 ].…”
Section: Pathogenesis Of Covid-19-related Skin Diseases and Therapeut...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an extract of Radix astragali, calycosin, was reported to inhibit neutrophil infiltration and protect heart integrity in isoproterenol-induced MI by synergizing with gallic acid ( 21 ). The cardioprotective effects of Panax ginseng or ginsenosides have been reported, through preventing MI and heart failure ( 22 ). The ethyl acetate extract of Ramulus cinnamomi and its bioactive substance cinnamic acid play a protective role in myocardial ischemia/reperfusion injury ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%